Evaluation of the impact of different size and shape polyethylene microplastic in Nile tilapia (Oreochromis niloticus) - ACAR, Ümit; ERDEN, Yavuz; GÜNAY, Sevilay; KESBİÇ, Osman Sabri; YILMAZ, Sevdan (Zenodo, 2023)
Plastic waste that is discharged into the aquatic environment can eventually break down into different size particles known as microplastics (MP). MPs have become a significant concern due to their potential negative effects on fish species. In this study, the effects of sublethal concentrations of various size and shape polyethylene microplastics (PE-MPs) on Nile tilapia were investigated on numerous levels, including hematological and DNA damage in blood. For this purpose, the phsysiological effects of freshwater fish species Nile tilapia  (Oreochromis niloticus) exposed to PE-MPs at control (0 mg/L), 5 mg/L, 10 mg/L, 25 mg/L and 50 mg/L for 14 days were investigated. In Nile tilapia PE-MPs exposure caused a significant decrease in hematological parameters. DNA damage in blood cells of fish exposed to PE-MPs was significantly higher than in the control group. Consequently, our findings show that PE-MPs affect many physiological parameters by causing oxidative stress-induced DNA damage in adult fish, and MPs should be considered a potent environmental pollutant when the rate in water is more than 10 mg/L for Nile tilapia.
Keywords: 13. Climate action; 14. Life underwater; 6. Clean water; 3. Good health